Problems That Traditional Health Practitioners And Western Health Practitioners Encounter In Interfacing - Favour Siema; Thizwilondi Madima; Isreal Siema (CV. RADJA PUBLIKA, 2025)
The study focused on the Problems that traditional health practitioners and western health practitioners encounter in interfacing .The interfacing of traditional health and western health care system has become increasingly important in recent years, particularly in Africa and other developing region however, the interfacing of traditional health practitioners and western health practitioners is often hindered by various challenges. Thus, the traditional health care system of South Africa, which was the primary health care for the indigenous people is mostly undermined by various religious groups. The youth and the scientific institution demonize the indigenous health care system and its practice as they associate it with witchcraft and other evil practices. Traditional health practitioners and western health practitioners have distinct diagnostic methods, philosophical approaches to health and illness. Western health practitioners focus on biomedical and scientific explanation while traditional health practitioners focus on spiritual and holistical aspects. The researcher observed a growing trend in the twenty-first century towards interfacing Traditional Health Practices (THPs) with Western doctors. It appears that basic health care systems were provided by traditional medical professionals in civilizations prior to the arrival of colonialism. The objective of the study was as follows, to examine problems that traditional health practitioners and western health practitioners encounter in interfacing. The study adopted an employ sociocultural theory. The study used a qualitative research design and was exploratory in nature. Data was generated using semi-structured interviews as data collection instruments.The finding of the shows that western practitioners do not believe that the ancestors do exist, and they undermine the diagnosing methods of traditional practitioner, as they say it is based on speculations due to lack of scientific results.The study recommend that education could make our community conscious of the conventional health care system and work to make youth and scientific groups be able to know and understand the importance of traditional health care system, integration of traditional health and western healthcare system and Funding traditional health care system.